Information literacy instruction that works : a guide to teaching by discipline and student population - Ragains, Patrick (Chicago : Neal-Schuman, an imprint of the American Library Association, 2013)
The need to find a broad range of information and the ability to analyze and use it effective has never been greater. Our understanding of students and how they learn; library technology; available resources-- these are all changing. This collection addresses how to meet with college and university students at all levels, teach research skills in subjects that are new to them, or develop a campus-wide IL initiative.
Setting the stage for college and university user education / Patrick Ragains and Mark Emmons -- Building strong relationships with faculty-librarian collaboration / Jean Caspers -- College and university freshman / Mark Emmons -- Community college students / Ann Roselle -- Students with disabilities / Adina J. Mulliken and Bernadette A. Lear -- Tailoring instruction for students in online and distance learning environments / Amy Elizabeth Hughes -- English literature / Janelle M. Zauha -- Art and art history / Peggy Keeran -- Film studies / Neal Baker -- Music / Laurie J. Sampsel -- History / Patrick Ragains -- Psychology / Nonny Schlotzhauer -- Anthropology / Catherine Cranston -- Scientific literacy / Elizabeth Berman -- Agricultural sciences and natural resources / Allison V. Level -- Engineering / Martin Wallace -- Business / Patrick Ragains -- Legal research for non-law students / Patrick Ragains -- Government information / Patrick Ragains -- Introduction -- Patent research / Suzanne L. Reinman.
Includes bibliographical references and index.
Keywords: Information literacy -- Study and teaching (Higher); Electronic information resource literacy -- Study and teaching (Higher); Academic libraries -- Relations with faculty and curriculum; Academic libraries -- Relations with faculty and curriculum; Electronic information resource literacy -- Study and teaching (Higher); Information literacy -- Study and teaching (Higher)